Characterizing the highly cited articles: A large-scale bibliometric analysis of the top 1% most cited research - Dorta-González, Pablo; Santana-Jiménez, Yolanda (Malaysian journal of library & information science, 2019)
We study the bibliometric or formal aspects influencing citations. In particular, we verify the existence or otherwise of bibliometric aspects which displayed significant differences between the group of top 1% most cited articles according to their field and year of publication (highly cited articles) and the remaining articles. This may allow scientific journals to have evidence when writing their submission rules for authors in order to maximize the impact of published articles. We did a large-scale analysis of around 10,000 scientific articles, from the period 2007-2016. A transversal analysis was conducted disaggregating the articles into more than one hundred scientific areas and two groups, each with a random sample of around five thousand documents. The first group comprised a random sample of the top 1% most cited articles in each field and year of publication (highly cited articles), and the second group a random sample of the remaining articles in the Journal Citation Reports (science and social science citation indexes in the Web of Science database). Highly cited articles differ from non-highly cited articles in most of the bibliometric aspects considered. There are significant differences, below the 0.01 level, between the groups of articles in many variables and areas. The highly cited articles are published in journals of higher impact factor (33 percentile points above) and have 25% higher co-authorship. The highly cited articles are also longer in terms of number of pages (10% higher) and bibliographical references (35% more). Finally, highly cited articles have slightly shorter titles (3% lower) but, contrastingly, longer abstracts (10% higher).